Urethral Polyembolokoilamania: An Unusual Manifestation of Behavioral and Psychological Symptoms of Dementia (BPSD) - Shafi, Reem M. A.; Suarez, Laura; Lapid, Maria I. (Case Reports in Psychiatry, 2018)
Behavioral and psychological symptoms of dementia (BPSD) have varied presentations and frequently occur throughout the trajectory of dementia. Hypersexuality and general disinhibition of societal and cultural norms are commonly documented in all types of dementia. However, sparse literature exists on polyembolokoilamania (insertion of foreign objects in bodily orifices) without a sexual component as a dementia-related symptom. We review an unusual case of a 94-year-old man who presented with urethral polyembolokoilamania without hypersexuality or other behavioral disinhibition. We highlight clinical considerations of managing urethral polyembolokoilamania in an elderly patient without a previous neurocognitive disorder diagnosis. A multidisciplinary team approach with input from Internal Medicine, Urology, Psychiatry, and Neurology lead to a comprehensive assessment of a patient that could have been managed solely as a surgical case. This spearheaded a formal diagnosis of neurocognitive disorder—guiding successful management, follow-up, caregiver education, and reduction of further harm.